Patrimônio icnofossilífero das vias públicas de São Carlos: levantamento da diversidade - Mendonça Júnior, Clóvis Heitor (Universidade Federal de São Carlos, 2023)
The Botucatu Formation is globally renowned for its ichnofossils. Originally part of a massive paleodesert from the early Cretaceous Period, the Formation consists of aeolian sandstones, with one of its main outcrop areas located in the municipality of São Carlos. Here, we aimed to conduct a survey and analysis of the ichnofossil diversity found in the public roads of the municipality, with the intention of documenting and preserving the fossil heritage present within them. Using the Street View tool on the Google Maps platform, a survey of locations featuring Botucatu Sandstone slabs was conducted. Subsequently, the obtained addresses were physically visited to assess the condition of the slabs and the presence or absence of fossil records. These sites were photographed to create a database. In total, a sum of 1285 locations containing Botucatu Sandstone slabs, some of which presented fossil traces were identified, ranging from invertebrates to mammals, theropod and ornithopod dinosaurs. There is a significant diversity within these groups, with 487 addresses displaying traces of invertebrates, 28 of mammals, and 21 of dinosaurs. Additionally, a loss of this collection was observed at a rate of 1% per month. Preserving this "open-air collection" is therefore of great scientific and national interest, with the present study potentially serving as a basis for drafting new laws for its preservation or as supplementary material for future studies on the fossil heritage of São Carlos.
Ichnofossiliferous heritage of public roads in São Carlos: survey of diversity
Keywords: Icnofósseis; Formação Botucatu; Cretáceo Inferior; Ichnofossils; Botucatu formation; Early Cretaceous; CIENCIAS BIOLOGICAS::ZOOLOGIA